Impact of proximal cytoplasmic droplets on quality traits and in-vitro embryo production efficiency of cryopreserved bull spermatozoa - Carreira, Janaina T. [UNESP] (2012)
Background: Proximal cytoplasmic droplets (PCDs), a remnant of germ cell cytoplasm, are common non-specific morphological defects in bovine semen. This study evaluated the effect of higher percentages of PCDs on the quality of frozen-thawed bovine semen, embryo production and early embryo development.Methods: Three ejaculates from each of five (group 1: PCD <= 1%, control) and eight adult Bos indicus bulls (group 2: PCD >= 24%) were analysed. Semen samples were examined for: post-thaw motility, vigour of movement, concentration, sperm morphology, slow thermoresistance test (STT), membrane integrity, acrosome status, mitochondrial function using fluorescent probes association (FITC-PSA, PI and JC-1) and sperm chromatin integrity using acridine orange assay. Two bulls from group 2, with 28.5% and 48.5% PCD, respectively, and three bulls from the control group, each with 0% PCD, were selected for IVF (in vitro fertilisation).Results: Semen analyses revealed a significant correlation (P < 0.01) between increased rates of PCD and sperm quality traits. Nevertheless, no differences were observed in sperm motility and vigour either before or after the STT or in the percentage of intact acrosomes (analysed by differential interference contrast microscopy (DIC) after STT), but membrane integrity, acrosome status (evaluated with FITC-PSA staining method after thawing) and mitochondrial function were reduced, when compared with group 1 (P < 0.05). The higher incidence of PCD was positively correlated to chromatin damage, especially after three hours of incubation at 37 degrees C. IVF showed similar results for bull C2 (group 1, control) and bull P2 (group 2, group with higher PCDs).Conclusion: Higher PCD levels influenced spermatozoa quality traits. IVF and embryo development data showed that cleavage, blastocyst formation and blastocyst hatching may have been influenced by the interaction of morphology traits and individual bull effects.